The Pathogenesis and Therapies of Striated Muscle Laminopathies - Brull, Astrid; Morales Rodriguez, Blanca; Bonne, Gisèle; Muchir, Antoine; Bertrand, Anne T. (Frontiers in Physiology, 2018)
Emery-Dreifuss muscular dystrophy (EDMD) is a genetic condition characterized by early contractures, skeletal muscle weakness and cardiomyopathy. During the last 20 years, various genetic approaches led to the identification of causal genes of EDMD and related disorders, all encoding nuclear envelope proteins. By their respective localization either at the inner nuclear membrane or the outer nuclear membrane, these proteins interact with each other and establish a connection between the nucleus and the cytoskeleton. Beside this physical link, these proteins are also involved in mechanotransduction, responding to environmental cues, such as increased tension of the cytoskeleton, by the activation or repression of specific sets of genes. This ability of cells to adapt to environmental conditions is altered in EDMD. Increased knowledge on the pathophysiology of EDMD has led to the development of drug or gene therapies that have been tested on mouse models. This review proposed an overview of the functions played by the different proteins involved in EDMD and related disorders and the current therapeutic approaches tested so far.